Case Study of Paralytic Shellfish Poisoning (PSP) Monitoring in Tropical Mangrove Estuaries : A Mini Review - Yurimoto, Tasuya; Chaweepak, Tidaporn; Sangrungruang, Koolvara (Hasanuddin University, 2024)
In recent years, the incidence of toxic plankton and bivalve poisoning that causes paralytic shellfish poisoning (PSP) has increased in Southeast Asian countries. Thailand is one of the most active bivalve aquaculture fisheries and needs to be prepared for this problem in the future. In this paper, we introduce a case of monitoring efforts on the Chanthaburi coast near the Cambodian border, where experimental PSP monitoring was conducted in water from 2013 to 2016, and a suitable monitoring system was considered in the region. As a result, we concluded that it is unlikely that the PSP problem will soon become serious in the region. However, in the surrounding waters, we must be aware of some invasive issues that may involve toxic plankton and cysts, such as ballast tank water from large vessels and transplantation of bivalves introduced from outside for aquaculture. Even if the waters are safe, PSP monitoring should continue on a small scale and at a low cost for an extended period.